Pemasaran Digital Jadi Kunci Peningkatan Penjualan Produk Kue Bangkit di Kelurahan Air Dingin - Hermita, Neni; Putra, Zetra Hainul; Alpusari, Mahmud; Alim, Jesi Alexander; Joleha, Joleha; Dahnilsyah, Dahnilsyah; Isjoni, Muhammad Yogi Ryantama; Rukaniya, Nurzilawati; Lubis, Nadhira Fahrani; Saputra, Rudi; Putri, Dwika Hanifah; Septiani, Ayu; Guisandro, Johannes; Aslamiah, Aslamiah; Waruwu, Riama; Afifi, Azza Ayu; Sihombing, Syeba Sekarini (Journal of Community Engagement Research for Sustainability, 2022)
Communities in the Air Dingin, Pekanbaru City, have a variety of sources of livelihood, and one of them is home-based businesses or micro, small, and medium enterprises (MSMEs) engaged in various sectors, both services, and products. However, many of these businesses have not developed optimally, especially in terms of promotion and sales. This is supported by the low level of technology literacy among business owners so that digital promotion and sales are not carried out optimally. Seeing this, Riau University students who are members of the Abdimas Integrated Kukerta (real work course) 2022 team carried out real work course to the people of the Air Dingin village to disseminate digital marketing channels to increase the creative economic potential of the Air Dingin village. The Kukerta team also assists to increase promotion and sales by designing product packaging and various important components that are included, as well as creating product sales accounts on various digital marketing channels such as Instagram, Facebook, and Whatsapp. In addition to improving the regional creative economy, this activity is also expected to introduce regional potential.